Diagnostic and Therapeutic Properties of Exosomes in Cardiac Fibrosis - Fan, Jiwen; Ren, Meng; He, Yuquan (Frontiers in Cell and Developmental Biology, 2022)
Cardiac fibrosis results from the deposition of excess extracellular matrix and the transformation of fibroblasts into myofibroblasts. It occurs during the progression of many cardiovascular diseases, adversely influencing both the clinical course and outcome of the disease. The pathogenesis is complex and there is no effective treatment. Exosomes are extracellular vesicles that mediate intercellular communication through delivering cargo to target cells. Recent studies have found that exosomes play an important role in cardiac fibrosis and can provide assistance in the diagnosis and treatment of cardiac fibrosis. The present review aimed to summarize the current knowledge of exosome-related mechanisms underlying cardiac fibrosis and to suggest potential therapy that could be used to treat the condition.